Higher Order Thingking Skills (Hots) dalam Konsep Integrasi Pendidikan Islam dan Sains - Hidayati, Baiq Titin; Saparudin, Saparudin (EduInovasi: Journal of Basic Educational Studies, 2024)
This article discusses the importance of Higher Order Thinking Skills (HOTS) in the integration between Islamic education and science. The HOTS concept helps students develop critical and creative thinking skills and link religious values ​​with science. This integration enables ethical assessment in the context of science and strengthens the understanding of the harmony between Islamic teachings and scientific principles. This research uses a literature study method to explore information related to the concept of HOTS and educational integration. HOTS is a complex thinking skill, involving analysis, evaluation and design. The integration of Islamic education and science combines two aspects to achieve a comprehensive understanding. The steps include integration through curriculum, syllabus, team teaching, assignments, and joint writing of work from various scientific disciplines. This integration not only enriches learning but also strengthens students' understanding of the harmony between science and religious values.